DAMPAK IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA DI KELURAHAN HINEKOMBE KABUPATEN JAYAPURA - Karma, Felix Yohanes; Rante, Harmonis; Poli, Agustina Ivonne (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
Regulation of the Ministry of Public Works and Public Housing Number 07/PRT/M/2018 concerning Self-Help Housing Stimulant Assistance is an implementation carried out through self-help housing quality improvement activities.The total population projected by the Central Statistics Agency in Jayapura Regency is 131,802 people, 17.19 thousand people are classified as poor, in other words there are 13.13 percent of the population classified as poor and occupying uninhabitable houses in Jayapura Regency. In this study,the aim to be achieved is to analyze the implementation and influence of the Self - Help Housing Stimulant Program on the welfare of the community in Hinekombe Village , Sentani District and analyze the factors that influence the success of the program.According to Tuwis Handayani,2016,in his research,the Impact of Self-Help Housing Stimulant Assistance Program Implementation on Improving Community Welfare,concluded that: Implementation of Self-Help Housing Stimulant Assistance Program in Sumberjo Village in 2015 was influenced by policies and program implementers.This research was conducted using a quantitative research approach with factor analysis where this analysis is an analytical technique that contains information about the grouping of factor variables which aims to filter out which variables are the most superior or the most dominant from several variables selected by the researcher,in addition to the results of factor analysis. can also be used to distinguish priority variables based on existing rankings. It can be concluded that the beneficiaries are of the opinion that the socialization of the BSPS program has been carried out,including obtaining information and assistance during the BSPS program. This BSPS program also influences the mindset and changes people's lifestyles.The relationship between people who received assistance from the BSPS program and those who did not receive assistance remained well established and did not change